MODERN INTERNATIONAL APPROACHES TO INVESTMENT POLICY OBJECTIVES STATEMENT AND EFFECTIVENESS MEASUREMENT - Bilenko, Tetyana (Proceedings of National Aviation University, 2013)
The article deals with the macroeconomic consequences of international requirements implementation in the sphere of investment policy objectives statement and efficiency measurement.